Mendorong Disiplin Keuangan di UMKM “Ngemil Berkah“: Pelaporan Keuangan yang Aksesibel dan Praktis - Khoirul Fuad; Hani Werdi Apriyanti; Hendri Setyawan; Winarsih Winarsih; Retno Tri Handayani (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This community service activity aims to provide assistance in designing and implementing a practical and easy-to-use financial reporting system. The activity was implemented through several stages: situation analysis to identify partner needs, training in basic financial transaction recording, assistance in preparing simple financial reports, and evaluation of the implementation of the developed system. The results of the activity indicate an increase in partners' ability to record financial transactions in a more orderly and systematic manner. Partners have also been able to prepare simple financial reports, such as profit and loss statements and cash flow statements, and have begun to implement a separation between business and personal finances. Overall, this activity has made a positive contribution to improving financial literacy and supporting business sustainability through more informed decision-making based on financial information.